Implementasi Konselor Sebaya Tersupervisi untuk Penguatan Dukungan Psikososial di Pesantren - Arbin Janu Setiyowati; Widya Multisari; Awalya Siska Pratiwi; Hengki Tri Hidayatullah (Yumary: Jurnal Pengabdian kepada Masyarakat, 2026)
Purpose: Islamic boarding schools in Indonesia, as boarding educational institutions, play a strategic role in developing the character and life skills of their students. The implementation of peer counsellors through a supervised prospective trainer scheme in Islamic boarding schools aims to strengthen the psychosocial support of students while simultaneously developing a sustainable intervention model appropriate to the Islamic boarding education. Research Methodology: The community service program was implemented using a variety of lecture methods to convey peer counselling concepts, guided discussions and assignments to deepen the material, workshops for practical counselling skills training, and mentoring to bridge the role of peer counsellors with school counsellors in service implementation. Results: The results showed an increase in post-test scores for all participants compared to the pre-test. This finding indicates that supervised training positively contributed to improving participants' reflective abilities and readiness to carry out their roles as peer counsellors. Conclusions: This community service activity proved effective in improving knowledge, skills, and readiness as peer counsellors, particularly in their understanding of psychosocial support and basic counselling skills such as empathy, reflective listening, and supportive communication. Limitations: Program limitations include the limited number of participants at one partner Islamic boarding school, the relatively short duration of mentoring, and the evaluation's inability to systematically measure the direct impact on the psychological well-being of the students receiving the services. Contributions: This program provides practical guidance for Islamic boarding schools in developing a friendly, accessible, and sustainable psychosocial support system through the empowerment of trained peer counsellors.